2004
DOI: 10.1161/01.str.0000128794.30660.e8
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Risk of Stroke and its Subtypes Among Middle-Aged Japanese Men and Women

Abstract: Background and Purpose-We examined sex-specific relationships of smoking with risk of total stroke and stroke subtypes in Asian populations because of the limited data available. Methods-A total of 19 782 men and 21 500 women aged 40 to 59 years who were free of prior diagnosis of stroke, coronary heart disease, or cancer and reported their smoking status were followed in the Japan Public Health There was a dose-response relation between the number of cigarettes smoked and risks of ischemic stroke for men. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 34 publications
(23 reference statements)
7
95
0
Order By: Relevance
“…Smoking was not found to be a risk factor for stroke in the past 26,27) ; however, recent large cohort studies in Japan, i.e. NIPPON DATA80, show a clear graded relationship between smoking and stroke [28][29][30] , as has been found in Western countries 31,32) . One explanation is that the magnitude of hypertension as a strong risk factor weakened due to the decline in population blood pressure level [3][4][5] .…”
Section: Risk Factors For Stroke and Chd In Japanmentioning
confidence: 97%
See 1 more Smart Citation
“…Smoking was not found to be a risk factor for stroke in the past 26,27) ; however, recent large cohort studies in Japan, i.e. NIPPON DATA80, show a clear graded relationship between smoking and stroke [28][29][30] , as has been found in Western countries 31,32) . One explanation is that the magnitude of hypertension as a strong risk factor weakened due to the decline in population blood pressure level [3][4][5] .…”
Section: Risk Factors For Stroke and Chd In Japanmentioning
confidence: 97%
“…Serum total cholesterol is not a risk factor for stroke, either cerebral hemorrhage or cerebral infarction, in Japan 29,[33][34][35][36][37] because most incidents of cerebral infarction in Japan are caused by hypertension and smoking 11,[21][22][23][24][25][26][27][28][29][30]33) . Although atherosclerosis of large vessels in the brain is caused by hypercholesterolemia 38) , the proportion caused by hypercholesterolemia is quite low in Japan 33) .…”
Section: Risk Factors For Stroke and Chd In Japanmentioning
confidence: 99%
“…Risk factors are dyslipidemia 10) , hypertension 11) , diabetes mellitus 8,9) , smoking habits 12) , family history 13,14) , male gender, and advanced age [15][16][17] . Arterial stiffness can be evaluated by various methods: stiffness parameter-, pulse wave velocity (PWV) 18) , carotid-femoral pulse wave velocity (cfPWV) 19) , heart-femoral pulse wave velocity (hfPWV) 20) , and brachial-ankle pulse wave velocity (baPWV) 21,22) are used as common noninvasive clinical indices, but these methods are limited because PWV is dependent on blood pressure at the measurement time.…”
Section: Introductionmentioning
confidence: 99%
“…An 11-year follow-up of the JPHC Study of 41,282 men and women aged 40 to 59 years 29) showed that the multivariate hazard ratios (95% CIs) for current smokers compared with never-smokers were 1.27 (1.05 to 1.54) for total stroke, 3.60 (1.62 to 8.01) for subarachnoid hemorrhage, and 1.66 (1.25 to 2.20) for ischemic stroke. The corresponding hazard ratios for women were 1.98 (1.42 to 2.77), 2.70 (1.45 to 5.02) and 1.57 (0.86 to 2.87).…”
Section: Smoking and Smoking Cessationmentioning
confidence: 99%